Producing the Past With the Digital: Virtual Reality as Remediation in History Museum's Presentation Practice - Lähteenmäki, Ilkka; Puurtinen, Marjaana (Wiley, 2026)
This paper examines contemporary museum practices in light of media and history theory, and understandings of representation. Through a content analysis of in-depth interviews with museum and IT professionals involved in creating a virtual reality (VR) exhibition piece, we demonstrate how theoretical concepts addressing the mediated nature of representations (remediation, immediacy, hypermediation) can be used to unpack cultural-history museum work in today's digital world. The analysis shows that our case example exhibition production process relied more on a division of labor between museum and IT experts, and on technology-driven decision-making than on joint discussions about on what grounds the different production steps are taken. Finally, we saw the urge to support museum visitors' engagement with the content and experience immediacy as one of the main goals for the whole project, and even something that overrides potential problematic issues about creating the representation itself.